Development of plastic bottle recycling machine / Mohamad Hilmi Kamisan - Kamisan, Mohamad Hilmi (2024)
Plastic is used by people around the world and plastic is also one of the materials that cause the most pollution on earth. Many products can be produced using plastic as materials such as plastic bottles. Most people use plastic bottles to store water and drink when they feel thirsty. After using the plastic bottle, they will throw the plastic bottle into the dustbin. However, some people irresponsibly do not manage plastic bottles properly after using them. For example, they will throw anywhere they want at their will even though they know what they are doing is wrong. Having a good tool to manage plastic bottles is needed to save the environment. The main objectives of this project are to design a plastic bottle recycling machine and to develop a motorized plastic cutter machine. In making a Plastic Bottle Recycling Machine, I need to research to create a proper and the best design with the limitations of the machines provided in UiTM and within my budget. Then, propose selected panels to approve my design and concept of the machine. After getting approval, I started to create the machine based on my approved design and made some advancements. Next, I will present to people my project after the machine fully operates. Lastly, make a report on the whole development of the Plastic Bottle Recycling Machine. This machine will benefit people by encouraging their recycling spirit and the machine has easy maintenance